Telomerase and cells youth. - Alexander Benavides Couto; Osvaldo Morales Mondeja (Medisur)
Telomerase is an enzyme formed by a protein-ribonucleic acid complex that allows telomere enlargement, non codifying DNA structures. Cellular activation allows its renovation and extends its life time and its possible number of divisions within the organism. These properties of the enzyme are an important factor in prevention and treatment of various diseases. Significant and updated data is collected about the study of this enzyme in ageing process, life time and properties.